Peran Kepuasan Konsumen dalam Memediasi Pengaruh Green Marketing dan Corporate Social Responsibility terhadap Loyalitas Konsumen Starbucks - I Irmawati; Bagas Arkanta Naufal Sandy (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to analyze and discuss the effect of green marketing and corporate social responsibility on consumer loyalty with consumer satisfaction as a mediating variable for Starbucks products. The population in this study is the consumer community of Starbucks products in the city of Surakarta through a sample of 170 respondents. Data collection techniques by distributing questionnaires. Data analysis in this study using Smartt PLS version 3.0. The technique used in the sampling of this research uses the purposive sampling technique and the technique in testing the data used in this study includes an external model consisting of convergent validity, discriminant validity, composite reliability, Cronbach alpha, and multicollinearity test as well as an internal model consisting of coefficients. determination, goods of fit, effect size test (f2), and hypothesis testing. The results in this study indicate that green marketing has a significant effect on consumer satisfaction, CSR has a significant effect on consumer satisfaction, consumer satisfaction has a significant effect on consumer loyalty, green marketing has a significant effect on consumer loyalty, CSR has a significant effect on consumer loyalty, consumer satisfaction plays a mediating role between green marketing on consumer loyalty, consumer satisfaction does not play a mediating role between CSR and consumer loyalty.